Strategic corporate social responsibility management for competitive advantage - Sousa Filho, José Milton de (2010)
Corporate social responsibility strategy and competitive advantage are important issues for the contemporary discussion on corporations in society when taking into account social and environmental impacts. Empirically, we can see that social responsibility strategies are associated with competitive advantages, such as attracting valuable employees as well as enhancing the company image and reputation. This paper presents a theoretical review that demonstrates the association between social strategy and competitive advantage through the formulation of social strategies that influence and are influenced by opportunities, resources, skills, corporation merits, industry structure and stakeholders. Based on the literature and a case study of Carrefour, a model is proposed for competitive advantages stemming from the formulation of social strategies, which are explained based on their elements and adaptation to societal expectations. This article seeks to enrich the discussion on the strategic management of social responsibility and contribute to the literature on Corporate Social Responsibility as well as Strategy and Competitive Advantage.